Buruh vs Perusahaan (Studi Kasus Konflik Buruh/ Pekerja Driver Go-Jek dengan PT Go-Jek Indonesia) - Randi Randi; Sonia Nurprameswari; Nita Apriliani (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2017)
The development of trade unions in Indonesia very rapidly. The development course of the growth of big companies in Indonesia. With the development of the number of workers increasing and labor rights is increasingly noteworthy either by the Government, the company and the workers ' organization itself. As for the focus in this paper, will discuss how the labour conflict drivers and PT gojek Go-Jek-based technology, and safety valves in the conflict. The reason for maintaining the social structure in the company needed a